2021
DOI: 10.1038/s41436-021-01140-x
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring best practice in genomics education and evaluation: reporting item standards for education and its evaluation in genomics (RISE2 Genomics)

Abstract: Purpose: Widespread, quality genomics education for health professionals is required to create a competent genomic workforce. A lack of standards for reporting genomics education and evaluation limits the evidence base for replication and comparison. We therefore undertook a consensus process with the aim of developing a recommended minimum set of information to support consistent reporting of the design, development, delivery and evaluation of genomics education interventions.Methods: Draft standards were der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…The development of Reporting Item Standards for Education and its Evaluation in Genomics will facilitate the development and delivery of genomics education and evaluation for nephrologists in future. 41 Results of our sensitivity analysis indicate that if patients were reviewed by a nephrologist together with a genetic counselor at the RGC (without requiring review by a clinical geneticist), the ICER would decrease to AU$2570, which is less than half the cost of the base case analysis. The cost of genomic pathways may also further decrease as price of sequencing falls.…”
Section: Discussionmentioning
confidence: 91%
“…The development of Reporting Item Standards for Education and its Evaluation in Genomics will facilitate the development and delivery of genomics education and evaluation for nephrologists in future. 41 Results of our sensitivity analysis indicate that if patients were reviewed by a nephrologist together with a genetic counselor at the RGC (without requiring review by a clinical geneticist), the ICER would decrease to AU$2570, which is less than half the cost of the base case analysis. The cost of genomic pathways may also further decrease as price of sequencing falls.…”
Section: Discussionmentioning
confidence: 91%
“…Our systematic review conducted prior to the development of TRUSTING revealed that there were few publications evaluating interventions explicitly designed to help HCPs discussing hereditary breast cancer risk and testing and that most failed to operationalise the skills that were included, outcome measures or analysis [12]. More recently, an influential report on the guidelines for genomics education has been published which might assist future programme developers [25]. Communication interventions that have been shown to change skills that transfer into a clinic setting and which are enduring need three essential components: elements that expand or solidify participants' knowledge base, communication skills development and personal awareness [7,26].…”
Section: Discussionmentioning
confidence: 99%
“…As such, we are heartened to see the rigorous approach employed by the RISE2 Genomics group. The leadership of G2NA fully endorses the framework put forth by Nisselle et al 1 and agrees that efforts are needed to advance harmonized work and build an evidence base for genomic education interventions and their evaluation. In addition, G2NA endorses the development of structured reporting guidelines (ie, Enhancing the QUAlity and Transparency Of health Research Network) as a priority to help further advance the state of the science for genomic education interventions and best practices in the field.…”
mentioning
confidence: 90%
“…Indeed, educational interventions are inconsistently described and reported in the literature. To address this gap, Nisselle et al 1 performed a structured scoping review to identify an initial item bank to chronicle the terms used to describe educational interventions and/or metrics used for evaluating outcomes and categorized items according to the logic model (ie, planning, development, engagement, and evaluation). Subsequently, a rigorous, iterative Delphi process was employed by drawing on the expertise of 38 international (ie, 11 countries, 5 continents) experts from diverse backgrounds to identify essential final standards (n = 31 items within the 4 logic model categories).…”
mentioning
confidence: 99%